Dance Movement Therapy dengan Media Tari untuk Menurunkan Stres pada Remaja - Kasih, Zelma Setya; Khusumadewi, Ari; Purwoko, Budi; Winingsih, Evi (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
Adolescents often face high emotional and psychological pressure due to academic demands, social relationships, and physical and hormonal changes. If not properly managed, stress during adolescence can negatively impact mental health. Therefore, adolescents require an effective approach to reduce their stress levels. This study aims to examine the effectiveness of Dance Movement Therapy (DMT) in lowering stress levels among adolescents. This research employs a systematic literature review (SLR) method, based on the PRISMA model, to analyze nine pertinent articles. The study collected data from various scholarly sources to evaluate how DMT can positively affect adolescents' psychological conditions. The results show that DMT is effective in reducing stress and anxiety levels, as well as enhancing adolescents' emotional well-being. Furthermore, factors such as social support and adolescents' emotional readiness also influenced the outcomes of the DMT intervention. This research demonstrates that dance movement therapy, which incorporates traditional dance, can serve as an effective intervention for reducing stress in adolescents.